A Treatise on High Protein Milk Ingredients - A Valued Food Additive for Food Products - Jana, Atanu; Balakrishnan, Smitha; Suthar, Janki; Patel, Amit (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
When used in food formulations, milk protein components provide not just nourishment but also specialised technological capabilities. Milk protein components are safe, natural proteins that can be used in a variety of nutritional and functional applications. The dairy and food industries are attempting to add value to their products in order to attract more customers for their innovative products. The objective of the chapter is to provide an insight to the readers regarding the scope of adding value to food products through use of novel, high protein milk ingredients having an array of functional properties and possible therapeutic virtues. Some salient functional properties of dairy protein ingredients include solubility, viscosity building, emulsification, heat stability, aeration, etc. Caseinates, co-precipitates, whey protein concentrates and isolates, milk protein concentrates, micellar casein, UF retentate powder, and other high protein dairy-based ingredients are highlighted in the chapter. Cheese analogues are a prime example of a product that requires high protein ingredients. UF retentate powders can be used to make wheyless cheese. Some of the disadvantages of conventional products, such as reduced cheese yield, wheying-off from yoghurt, and body breakdown during storage, can be overcome by incorporating high protein dairy ingredients into the food product formulation. The applications of such high protein tailor-made ingredients in dairy and food products have been discussed in this chapter.